EVALUASI TEKNIS SISTEM FOTOVOLTAIK HIBRIDA OFF-GRID UNTUK SUBSTITUSI DAYA PEMAKAIAN SENDIRI PADA INSTALASI WTP PLTU MALINAU - Arif, Muhammad; Wibowo, Eri; Nurdin, Muhammad Firdan (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2025)
A standalone hybrid photovoltaic (PV) system integrated with lithium-ion battery storage was designed and evaluated to substitute the auxiliary power demand of the Water Treatment Plant (WTP) at the Malinau Coal-Fired Power Plant (2x3 MW), North Kalimantan, Indonesia. Through PVsyst 8.0 simulations utilizing local irradiance, load profile, and shading parameters, the system achieved an annual solar fraction of 94.3% and a performance ratio (PR) of 67.91%, delivering 120.13 MWh/year of useful energy. Battery round-trip efficiency reached 94.9%, indicating minimal energy loss during storage. These results demonstrate the system's technical viability for replacing fossil-based auxiliary energy in tropical industrial settings. Further implications include cost savings, emission reduction, and enhanced reliability.